Identification and quantification of phosphodiesterase-5 inhibitor as falsified in natural Malaysian herbal aphrodisiacs sold in some Beninese markets. - ASSANHOU, Assogba Gabin (My University, 2022)
Objective: Nowadays, there have been several reports of herbal products falsified with well-known synthetic molecules, leading to harmful health consequences for the consumer. The aim of this study was to assess the profile of ‘natural' herbal aphrodisiacs in the local markets of the municipalities of Cotonou and Abomey-Calavi in Benin and to screen some of them for the presence of additives such as sildenafil and tadalafil. Methods: A non-probability survey was conducted to identify the available aphrodisiacs and their characteristics. Some of them were then selected for analysis. Thin Layer Chromatography (TLC) was adopted for qualitative detection. The TLC positive extracts were then analyzed by HPLC on a C18 column with a mobile phase consisting of a mixture of 0.05M phosphate buffer (pH 5.8), acetonitrile and methanol (30:50:20). The Detection was performed at 290 nm. Results: Seventy-seven aphrodisiacs were identified and from these, 18 were selected for analysis. Six of them were adulterated with tadalafil. The concentration of tadalafil in the samples was 1.7 to 4.6 times higher than the recommended dose of 20 mg. Conclusion: This work opens the door to the need to control ‘‘natural’’ labeled products in order to ensure their quality.
Keywords: Herbal aphrodisiacs; Falsification; PDE-5 Inhibitors